Криптосистеми з квантовим розподілом ключів - Скічко, Д. В. (My University, 2021)
The object of research is cryptosystems with quantum key distribution and their efficiency. Research methods - theoretical, axiomatic and specific analysis. The result is conclusions about cryptosystems with quantum key distribution, quantum computer and assumptions about further ways of their development.The subject of research is to study the current state of development of cryptosystems with quantum key distribution, quantum computing and quantum computer. Assess the threats of the quantum computer to modern cryptography and classical key distribution algorithms. This paper reveals the theoretical basis for quantum computing and quantum computers. The architecture of the quantum computer and the principles of its operation are studied. The basic principles of quantum theory and quantum mechanics, which are the basis of quantum computing, are considered. A theoretical comparison of the classical computer and its computing capabilities in relation to the current state of the quantum computer and its computing capabilities. Modern quantum algorithms with quantum key distribution such as: BB84, BB92 and examples of cryptosystems in which these algorithms can be used are considered and analyzed.
Keywords: квантовий комп'ютер; криптографія; квантовий розрахунок; кубіти; квантова інформація; квантові схеми; постквант